NICU and postpartum nurse perspectives on involving fathers in newborn care: a qualitative study - Katharine W. Buek (BMC Nursing, 2021)
Abstract Background Perinatal care nurses are well positioned to provide the education and support new fathers need to navigate the transition to fatherhood and to encourage positive father involvement from the earliest hours of a child’s life. To effectively serve fathers in perinatal settings, it is important to understand the attitudes, beliefs, and behaviors of healthcare providers that may encourage and engage them, or alternatively alienate and discourage them. Methods This qualitative study involved structured interviews with ten NICU and postpartum nurses from hospitals in two large Texas cities. The interview protocol was designed to elicit descriptive information about nurses’ attitudes and beliefs, sense of efficacy and intention for working with fathers, as well as their father-directed behaviors. Nurses were recruited for the study using a purposive sampling approach. Interviews were conducted by telephone and lasted approximately 25 to 35 min. Data were analyzed using a qualitative descriptive approach. Results Overall, study participants held very positive subjective attitudes toward fathers and father involvement. Nevertheless, many of the nurses signaled normative beliefs based on race/ethnicity, gender, and culture that may moderate their intention to engage with fathers. Participants also indicated that their education as well as the culture of perinatal healthcare are focused almost entirely on the mother-baby dyad. In line with this focus on mothers, participants comments reflected a normative belief that fathers are secondary caregivers to their newborns, there to help when the mother is unavailable. Conclusions Nurse attitudes and practices that place mothers in the role of primary caregiver may be interpreted by fathers as excluding or disregarding them. Further research is needed to validate the results of this small-scale study, and to assess whether and how provider attitudes impact their practices in educating and engaging fathers in newborn care.